WHO WORKS MORE, AND WHO WORKS SMARTER? COMPARING JUDICIAL PERFORMANCE IN EUROPE - Spaić, Bojan; Djordjević, Mila (Pravni zapisi, 2024)
This paper (1) analyzes the existing theoretical framework for understanding the relationship between the judicial performance and judicial efficiency, (2) compares the judicial performances in Serbia, Croatia, Slovenia, France, Austria, and Norway for the year 2020, (3) compares the judicial performances in different instances in Serbia for the same year, and (4) examines the performance standards that are set by law for Serbian judges. The authors conclude that in 2020 Serbian judges resolved more cases in all instances (there is a higher number of resolved cases per judge only in Austria, in first instance), while at the same time falling short of the caseload standards set in Serbian law. Also, the study found excessive difference in the performance of Serbian courts, but that does not affect the evaluation of judg- es, since 485 evaluated judges out of 505 got the rating “exceptionally successfully performs the function of judge” for the year 2020.
Keywords: efficiency of justice; judicial performance; evaluation of judges; judicial organization